Do diamond stocks shine brighter than diamonds? - Vera Jotanovic; Rita L. D'Ecclesia (Journal of Risk and Financial Management, 2019)
This paper addresses two practical investment questions: Is investing in the diamond equity market a more feasible and liquid alternative to investing in diamonds? Additionally, is diamond equity affected by polished diamond prices? We assemble an original database of diamond mining stock prices traded on main stock exchanges in order to assess their relationship with diamond prices. Our results show that the market of diamond-mining stocks does not represent a valid investment alternative to the diamond commodity. Diamond equity returns are not driven by diamond price dynamics but rather by local market stock indices.
Keywords: G10; G11; G15; 330; diamond stocks; diamond prices; investment asset; capital asset pricing model